2019
DOI: 10.1101/703132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Consolidation of reward memory during sleep does not require dopaminergic activation

Abstract: Sleep enhances memories, especially, if they are related to future rewards. Although dopamine has been shown to be a key determinant during reward learning, the role of dopaminergic neurotransmission for amplifying reward-related memories during sleep remains unclear. In the present study, we scrutinize the idea that dopamine is needed for the preferential consolidation of rewarded information. We blocked dopaminergic neurotransmission, thereby aiming to wipe out preferential sleep-dependent consolidation of h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…We have recently followed up this work to investigate whether dopamine is necessary for this effect by using the dopamine d2like receptor blocker sulpiride ( [143], bioRxiv). Otherwise relying on the exact same procedures, we found that blocking dopaminergic neurotransmission with a dose of sulpiride that has been shown to block~60% of d2-like receptors [144] did not affect the highly over lowly rewarded memory advantage of sleep.…”
Section: Dopaminergic Neuromodulationmentioning
confidence: 99%
“…We have recently followed up this work to investigate whether dopamine is necessary for this effect by using the dopamine d2like receptor blocker sulpiride ( [143], bioRxiv). Otherwise relying on the exact same procedures, we found that blocking dopaminergic neurotransmission with a dose of sulpiride that has been shown to block~60% of d2-like receptors [144] did not affect the highly over lowly rewarded memory advantage of sleep.…”
Section: Dopaminergic Neuromodulationmentioning
confidence: 99%